2021
DOI: 10.15761/mcrr.1000173
|View full text |Cite
|
Sign up to set email alerts
|

Molecular insights into the docking of N-palmitoyl serine (Palmi-Ser) interaction with the nuclear receptor subfamily 4 group A member 2 (NR4A2): Effect of Palmi-Ser on survival rate in the Drosophila model of Parkinson's disease

Abstract: Alternative therapy with medical devices using high-voltage electric potential (HELP) to generate an electric field (EF) is common in Japan. In a previous study, HELP exposure-induced upregulation of N-palmitoyl serine (Palmi-Ser) and N-oleoyl serine (Oleo-Ser) in the plasma of healthy individuals was observed. Recently, we found that Oleo-Ser-stimulated fatty acid-binding protein 1 (FABP1) mRNA expression is sensitive to the peroxisome proliferator-activated receptor-alpha (PPAR-α) antagonist. To discover pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…If this occurs in vivo , EFs may alleviate GD symptoms by preventing protein aggregation. Our previous study showed that EF treatment elevated N-palmitoyl serine levels in healthy humans, which extended the lifespan of PD model flies (Nakagawa-Yagi et al, 2021). Further studies using Drosophila models of neurodegenerative diseases, such as PD and GD, should be conducted for clarifying the effect of ELF-EFs.…”
Section: Discussionmentioning
confidence: 98%
“…If this occurs in vivo , EFs may alleviate GD symptoms by preventing protein aggregation. Our previous study showed that EF treatment elevated N-palmitoyl serine levels in healthy humans, which extended the lifespan of PD model flies (Nakagawa-Yagi et al, 2021). Further studies using Drosophila models of neurodegenerative diseases, such as PD and GD, should be conducted for clarifying the effect of ELF-EFs.…”
Section: Discussionmentioning
confidence: 98%